Epithelioid malignant peripheral nerve sheath tumour – a case report of rapid progression - Woźniacki, Piotr; Drucis, Kamil; Pęksa, Rafał; Jastrzębski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2009)
Malignant peripheral nerve sheath tumour (MPNST) is a rare tumour, which accounts for 5-10% of soft tissue sarcomas. We present a case of epithelioid malignant peripheral nerve sheath tumour (EMPNST) also known as epithelioid malignant schwannoma, which accounts for less than 5% of MPNSTs, located in the crus. Before the patient’s admission to the Surgical Oncology Department fine needle aspiration (FNA) examination revealed melanoma malignum cells and the patient was qualified for surgical treatment. During the operation the infiltration of muscles and tibia was noticed and final histological examination revealed EMPNST. Cyto-reduction surgery was performed. During the following month rapid progression was observed (additional large tumour located in the groin); thus amputation of the extremity was performed. However, the tumour localized in the groin turned out to be already inoperable, because of infiltration of the femoral artery. The authors underscore the rare type of the sarcoma, diagnostic difficulties, prognostic factors, rapid progression and the choice of treatment.